The Role of Company Size in Moderating the Effect of Profitability, Profit Growth, Leverage, and Liquidity on Earnings Quality - Lestari, Siska Puji; Khafid, Muhammad (Universitas Negeri Semarang, 2021)
This study aims to determine the effect of profitability, earnings growth, leverage, and liquidity on earnings quality with company size as a moderating variable. The population in this study was 65 property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. The sample selection used a purposive sampling technique and selected 44 companies with 132 units of analysis. The analysis techniques used descriptive statistical analysis, inferential analysis, and moderated regression analysis. The results showed that leverage and liquidity had a positive effect on earnings quality. While profitability and earnings growth have no effect on earnings quality. Company size is able to weaken the effect of profitability, leverage, and liquidity on earnings quality. The conclusion of this study is that the quality of the company’s earnings will increase if the company can maintain the level of leverage and the level of company liquidity. However, the quality of company earnings will decrease when the size of the company is large and affects the company’s leverage and liquidity on the quality of the company’s earnings. Keywords: Profitability; Profit Growth; Leverage; Liquidity; Profit Quality; Company Size